KOMUNIKASI BUDAYA ANTARA JEPANG DAN INDONESIA - ROBIHIM, ROBIHIM (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
This paper not only emphasizes how people of Indonesia and Japan differ in speech, but how they act anta rorang and how they follow the rules that govern the behavior of covert community members. It has been known for thousands of anecdotes about intercultural misunderstandings due to communication between people from different cultures. Because of the large number of pairs of cultures, and because of the possibility of misunderstandings based on the form of verbal and nonverbal behavior between each pair of culture as large, then there are many anecdotes about things that might be made about intercultural. One who successfully characterized the Japanese are Shinto and Buddhism teachings. Shinto is Japans original teachings of Buddhism while originating from China is delivered to Japan by Chinese traders who came to Japan and Japanese students sent at that time to study Buddhism. However, strangely it is not Buddhism developed in China, but highly developed in Korea and Japan. Buddhism later gave birth to Confucian teachings, which further the doctrine is taught by a Chinese sage, named Kong Zui. He taught moral ethics of the ideal system to build relationships within the family and the state in a harmonious unity.Keywords: Communication, behavior, Japanese, Sundane